Dietary Intake and Pneumococcal Vaccine Response Among Children (5–7 Years) in Msambweni Division, Kwale County, Kenya - Migliore, Eleonora; Amaitsa, Vivian K.; Mutuku, Francis M.; Malhotra, Indu J.; Mukoko, Dunstan; Sharma, Anika; Kalva, Prathik; Kang, Amrik S.; King, Charles H.; LaBeaud, A. Desiree (Frontiers in Nutrition, 2022)
Vaccine and sufficient food availability are key factors for reducing pneumonia outbreaks in sub-Saharan Africa. In this study, the 10-valent pneumococcal conjugate vaccine (Synflorix® or PCV10) was administered to a child cohort (5-7 years old, n=237) in Msambweni, Kenya, to determine relationships between dietary intake, nutritional/socioeconomic status of mothers/caregivers, and vaccine response. 7-day food frequency questionnaire (FFQ), dietary diversity score (DDS) and single 24-h dietary recall were used to address participants’ dietary assessment and nutritional status. Individual food varieties were recorded and divided into 9 food groups as recommended by Food and Agriculture Organization. Anthropometric measurements, nasopharyngeal swabs and vaccine administration were performed at the initial visit. Participants were followed 4-8 weeks with a blood draw for pneumococcal IgG titers assessed by Luminex assay. Chronic malnutrition was prevalent in the cohort (15% stunting, 16% underweight). Unbalanced dietary intake was observed, with mean energy intake 14% below Recommended Dietary Allowances (1822Kcal) for 5-7 years age range. 72% of the daily energy was derived from carbohydrates, 18% from fats and only 10% from proteins. Poor anthropometric status (stunting/underweight) was associated with low socioeconomic/educational status and younger mother/caregiver age (p<0.002). Limited intake of essential micronutrients (vitamins A, E, K) and minerals (calcium, potassium) associated with low consumption of fresh fruits, vegetables, and animal source foods (dairy, meat) was observed and correlated with poor vaccine response (p<0.001). In contrast, children who consumed higher amounts of dietary fiber, vitamin B1, zinc, iron, and magnesium had adequate vaccine response (p<0.05). Correlation between higher dietary diversity score (DDS), higher Vitamin E, K, Zinc intake and adequate vaccine response was also observed (p<0.03). Overall, this study highlights ongoing food scarcity and malnutrition in Kenya and demonstrates the links between adequate socioeconomic conditions, nutrition status and vaccine efficacy.